Efek Smoothies Piselon (Pisang, Semangka dan Melon) terhadap Tekanan Darah Pasien Hipertensi: Effect of Piselon Smoothies (Banana, Watermelon and Melon) on Blood Pressure of Hypertensive Patients - Sartono; Meliana, Endang; Telisa, Imelda (Poltekkes Kemenkes Palu, 2024)
The objective of this research is to investigate if the consumption of banana, watermelon, and melon Smoothies Piselon has any impact on the blood pressure measurements of hypertensive patients undergoing treatment at Puskesmas Sinar Baru, Bangka Regency. This research is a pre-test and post-test study with a two-group design with a quasi-experiment with a control group. There are 47 subjects in the intervention group, matched by an identical number in the control group. The examination of the gathered data employed both univariate and bivariate analytical techniques.The findings from this investigation indicate that the formula containing banana, watermelon, and melon identified as Formula 1 was favored by panelists, particularly for its visual appeal, scent, flavor, and consistency. In the cohort treated for hypertension, the initial average systolic blood pressure was recorded at 158.19 mmHg and decreased to 152.62 mmHg post-treatment. Similarly, the average diastolic blood pressure was reduced from 94.89 mmHg to 90.81 mmHg. In the examined cohorts, a substantial alteration in systolic and diastolic blood pressures was discerned, as demonstrated by a t-dependent test with a statistically significant result, producing a p-value of 0.000 (p<0.05). It was conclusively determined that the intake of Smoothies Piselon markedly decreased blood pressure, with reductions averaging 5.57 mmHg in systolic and 4.08 mmHg in diastolic measurements.